Alterações no comportamento tático, respostas fisicas e fisiológicas em pequenos jogos com igualdade e superioridade numérica no futebol - Borges, Eduardo de Paula Amorim (2022)
To increase soccer performance, contemporary training methods are used, based on the use of small games, which aim to improve, for example, the technical and tactical skills of the players, depending on the manipulation of variables such as the number of players, limitation of ball touches and others. However, little has been investigated about tactical and physical-physiological parameters of Small Games situations where the number of players between teams is unbalanced. Therefore, the objectives of the present research were: to carry out a narrative review about small games in football and to analyze the tactical and physical-physiological behavior of under-15 and under-17 athletes from small games (SSGs) played with equality. numerical and numerical superiority in the offensive phase in soccer players. The narrative review showed that SSGs are pedagogical tools used in training sessions to improve players' tactical, technical, physical and psychological skills in formal game-like environments. The use of reduced games has advantages in the teaching-learning-training process of football, as long as the coach understands which game variables must be manipulated to achieve his goals. Thus, the effectiveness of small games as pedagogical tools depends on their multiple configurations, such as the composition of teams, the number of players per team, the size of the field and the manipulation of game rules. These game settings must be aligned with the goals of the coach and the team, and meet the athletes' ability to solve problem situations, based on their tactical knowledge. When considering the analysis of the tactical and physical behavior of the second objective, 14 athletes from the under-15 categories and 14 athletes from the under-17 category were